Health Care Burden of Bronchopulmonary Dysplasia Among Extremely Preterm Infants - Mowitz, Meredith E.; Ayyagari, Rajeev; Gao, Wei; Zhao, Jing; Mangili, Alexandra; Sarda, Sujata P. (Frontiers in Pediatrics, 2019)
Background: Infants born extremely preterm are at high risk of developing bronchopulmonary dysplasia (BPD). This study aimed to assess the incremental health care burden of BPD and associated comorbidities among extremely preterm infants in the United States. Methods: Health service claims in the Premier Perspective database were retrospectively analyzed for infants born at ≤28 weeks gestation who were admitted to neonatal intensive care during birth hospitalization and survived to a postmenstrual age of ≥36 weeks. Results: Of the 12,017 infants included, 4904 (40.8%) had BPD. BPD increased with decreasing gestational age (GA): 67.4% of infants born at <24 weeks GA had BPD vs. 28.7% of those born at 27–28 weeks. Infants with BPD had significantly longer hospital stays following birth than those without (mean [standard deviation (SD)] 102 [34] vs. 83 [24] days, respectively, P < 0.001), and incurred higher total charges (mean [SD] 799,499 [535,528] vs. 588,949 [377,137], respectively, P < 0.001). During their first year, infants with BPD had a higher in-hospital mortality rate than those without (1.9% vs. 0.6%), and were more likely to have two or more hospital encounters following birth hospitalization (58.0% vs. 48.2%,). Among infants who had two or more encounters after discharge, those with BPD experienced a higher percentage of pulmonary symptoms than those without (46.3% vs. 38.9%). Comparison with infants who did not have BPD, retinopathy of prematurity, or intraventricular hemorrhage showed that BPD is the main complication contributing to increased length of stay, costs, in-hospital mortality, and additional health care encounters. Conclusion: BPD is a key contributor to the large health care burden associated with extremely preterm birth.